Pengaruh Kualitas Informasi, Persepsi Kemudahan, Kegunaan, dan Keamanan Terhadap Minat Penggunaan Aplikasi Tangeranglive di Tangerang Selatan - Made Sandy Wijaya; Agung Edi Rustanto; Yahya Rachmana Hidayat; Siti Mariam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of information quality, perceived ease of use, perceived usefulness, and perceived security on the intention to use the TangerangLive application in South Tangerang City. TangerangLive is a digital public service application developed by the Tangerang City Government to facilitate public access to various government services in an effective and efficient manner. This study employed a quantitative approach using a survey method. The research population consisted of residents of South Tangerang City who were familiar with and had previously used the TangerangLive application. A total of 250 respondents were selected using a purposive sampling technique. The results indicate that information quality, perceived ease of use, perceived usefulness, and perceived security have a positive and significant effect on the intention to use the TangerangLive application. Both partially and simultaneously, these four variables make a significant contribution to increasing users' intention to adopt the application. This study is limited by its geographical scope, as it focuses only on South Tangerang City. Therefore, future research is recommended to expand the study area, employ a longitudinal approach, and incorporate additional relevant variables to obtain more comprehensive findings. The results of this study are expected to contribute to the development of digital public services and provide practical recommendations for local governments to improve the quality of the TangerangLive application and encourage greater public adoption.